The Interactive Effects of Personal Traits and Experienced States on Intraindividual Patterns of Citizenship Behavior - Ilies, Remus; Scott, Brent A.; Judge, Timothy A. (Academy of Management Journal, 2006)
An experience-sampling study investigating the dynamic process through which personal traits and affective and attitudinal states experienced at work influence intraindividual patterns of organizational citizenship behavior over time generally supported hypotheses. First, at the intraindividual level, experience-sampled positive affect and job satisfaction predicted experience sampled reports of organizational citizenship behaviors over time. Second, cross-level interaction between agreeableness and positive affect predicted organizational citizenship behavior. Compared to less agreeable employees, agreeable employees reported both engaging more often in organizational citizenship behavior and more consistent patterns of such behavior; their engagement in these behaviors was less dependent on their momentary positive affect.